Shoulder-Pacemaker Treatment Concept for Posterior Positional Functional Shoulder Instability: A Prospective Clinical Trial. Issue 9 (July 2020) - Moroder, Philipp; Plachel, Fabian; Van-Vliet, Heiko; Adamczewski, Christiane; Danzinger, Victor
Background: Pathological muscle activation patterns of the external rotators and periscapular muscles can result in posterior positional functional shoulder instability (PP-FSI). In several patients, physical therapy and surgical treatment are not successful. Purpose: The shoulder-pacemaker treatment concept was evaluated prospectively in patients with PP-FSI and previously failed conventional therapy attempt. Study Design: Case series; Level of evidence, 4. Methods: A negative selection of 24 consecutive cases of noncontrollable PP-FSI in 16 patients with previously failed conventional therapy were included in this prospective study. The shoulder-pacemaker treatment consisted of an electrical muscle stimulation–based therapy protocol with 9 to 18 one-hour treatment sessions. Two patients were excluded because of nonadherence to the training schedule, leaving a final study cohort of 21 cases in 14 patients. Follow-up included assessment of clinical function, impairment during daily activities and sports, satisfaction, Western Ontario Shoulder Instability Index (WOSI), Rowe score, and Subjective Shoulder Value at 0 weeks, 2 weeks, 4 weeks, 3 months, 6 months, 12 months, and 24 months after intervention. Results: WOSI, Subjective Shoulder Value, and Rowe score showed a highly significant improvement at all time points of follow-up ( P < .001). Young age ( P = .005), low weight ( P = .019), shoulder activity level ( P = .003), unilateral affliction ( P = .046), and higher baseline WOSI score ( P = .04) were associated with a better treatment effect. Cases with increased glenoid retroversion, posterior scapulohumeral decentering, and dysplastic bony glenoid shape showed a trend toward shorter treatment effect duration. No complications during the intervention or follow-up period were observed. Conclusion: The shoulder-pacemaker therapy concept is an effective treatment with rapid improvement and sustained outcome over the course of 2 years in patients with noncontrollable PP-FSI with previously failed conventional treatment. Young and more athletic patients with lower weight and unilateral pathology respond best to the treatment.